UPAYA PENCEGAHAN COVID-19 PADA LANSIA DI KELURAHAN ANDALAS KOTA PADANG - Ayulia Fardila Sari ZA; Shelvy Haria Roza; Ulfah Adesty Ayuningtias (BULETIN ILMIAH NAGARI MEMBANGUN, 2020)
The Corona Virus Disease 2019 (Covid-19) spread so fast to the various countries and cause death. One of the susceptible groups that can be infected by this virus is the elderly. There were 190,000 cases (95%) in the elderly of the 60th and over until April 30, 2020. The mortality rate of COVID-19 cases in the Indonesian elderly got the second-highest number (34.2%) of 302 people. The positive confirmations of COVID-19 in West Sumatra have reached 148 people, with 18.18% from the elderly group. Padang City is the city with the highest number of positive confirmations in West Sumatra, which there were 99 people got infected. Andalas Urban Village in the East Padang Sub-district has the highest elderly population in the Padang city; its total is 8,250 people. The efforts to maintain the elderly's health were through the elderly Integrated Healthcare Center at the neighborhood and hamlet levels. The purpose of community service was to increase the knowledge and awareness of the elderly and the accompanying family in maintaining health, especially in the preventing of Covid-19. This method is to educate the elderly cadres and health promotion to the elderly. The activity result is implementing Covid-19 preventive education to the three elderly cadres in Andalas Urban Village, Padang City. This activity also encourages the implementation of delivery package to the elderly's houses. The package contains honey, snacks, liquid soap, masks, and a brochure on Covid-19 prevention to the elderly.